Dampak Pengeboran Minyak Ilegal Terhadap Perubahan Tatanan Sosial Masyarakat Gampong Mata Ie Kecamatan Ranto Peureulak Kabupaten Aceh Timur - Vinia Alvina; Husna, Nurul (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
This writing aims to examine the factors that cause changes in the social order of society as a result of oil drilling and to examine the impact of illegal oil drilling on changes in the social order of society. The research method used in writing this thesis is qualitative. The factors that cause social changes in society as a result of illegal oil drilling are economic factors, community ignorance, the lack of available employment opportunities and weakening of relationships between residents. The negative impacts that arise due to oil drilling on physical environmental conditions are that villages are dry, the environment is polluted, the quality of the soil becomes hard, infertile plants are affected by oil waste, air pollution causes people to be more susceptible to disease, especially for workers who have asthma in direct contact with oil wells containing negative substances H2O (toxic gas) and negative impacts on the community's physical environment.